Poverty and racism: How we think and talk about poverty reduction matters - Alhassan, Jacob Albin Korem; Christopherson-Cote, Colleen (Engaged Scholar Journal, 2024)
There is a close connection between poverty and racism yet insufficient literature integrates anti-racist praxis in poverty reduction work. We draw here on the first stage of a project that brought together the Saskatoon Poverty Reduction Partnership (SPRP) and the Saskatchewan Anti-Racism Network (ARN) to explore possibilities for better alignment of the advocacy of both organizations. We conducted a media discourse analysis of 462 newspaper articles systematically extracted from grey literature site Factiva on how poverty reduction is framed and how media reportage links poverty and racism in Saskatchewan. We find that very few newspaper articles published on poverty reduction focus on the connections between poverty and racism. Additionally, there are four dominant ways of framing poverty reduction namely: i) the cost framing of poverty reduction ii) the shame and embarrassment framing of poverty reduction iii) the human rights framing of poverty reduction and iv) the root cause analyses of poverty reduction. The cost and shame framings of poverty reduction may further marginalize or de-center those living in poverty compared to the human rights and root cause framings. More explicit connection needs to be made between poverty reduction work and anti-racist praxis for effective advocacy.